P-TsOH mediated solvent and metal catalyst free synthesis of nitriles from aldehydes via Schmidt reaction. Issue 23 (7th June 2017) - Mitra, Bijeta; Pariyar, Gyan Chandra; Singha, Rabindranath; Ghosh, Pranab
Graphical abstract: Highlights: Safe and mild reaction condition for a wide variety of substrates. Solvent and metal catalyst free. Simple and easy workup procedure. Cost and time effective. Environmental friendly. Abstract: A new and efficient protocol for the conversion of aldehyde into nitriles by modified Schmidt reaction. The reaction is carried out under solvent free condition using sodium azide as a source of nitrogen and catalysed by p -toluene sulphonic acid in presence of silica surface with no side product. This transformation gives good to excellent yield for numerous aromatic, aliphatic and heterocyclic nitriles using very simple reagent. This method has avoided the use of transition metal catalyst, toxic cyanide, hazardous solvent and offers a greener, simple and environment friendly procedure.